Investigating Saudi university medical students’ English language difficulties: a needs analysis study - Alrashed, Mohammed; Abdel Latif, Muhammad M. M. (Frontiers in Medicine, 2025)
An important dimension in the education of health professionals is developing their English language performance to help them meet academic and professional needs. Though understanding Saudi university medical students’ English language needs is key to helping them perform well in their academic studies and future workplaces, there has been scarce research on these needs. The present study investigated Saudi university medical students’ English language difficulties, the strategies they use for overcoming these difficulties, their evaluation of the English language instruction received at their colleges and perceptions of their English language needs. The study drew upon surveying students’ language needs through using a 25-item questionnaire with four sections assessing the target dimensions. Two hundred and 55 students completed the questionnaire. The students have some difficulties when completing productive language tasks and when processing content explained or written fully in English. Their highest language needs relate to improving medical terminology and English speaking, but their lowest language need concerns listening. A few significant gender-related differences were noted. The English language instruction provided to the students studying medicine could be reformed through giving more attention to improving their productive language skills and helping them communicate fluently using target medical terminology.